2016
DOI: 10.3892/ol.2016.4396
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 in human clear cell renal carcinoma: Expression, function and prognostic significance

Abstract: Abstract. Targeting protein for Xenopus kinesin-like protein 2 (TPX2) is a microtubule-associated protein. TPX2 is considered to be an important gene in tumorigenesis; however, the particular function of TPX2 in the development of human renal cell carcinoma (RCC) is unknown. In the present study, the expression, function and prognostic significance of TPX2 in human RCC was analyzed. A total of 286 tissue samples from patients with RCC who had undergone nephrectomies were utilized. Subsequently, the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In contrast, TPX2 knockdown inhibited cell proliferation and invasion through decreased Akt phosphorylation and expression of MMP-9 and cyclin D1 ( 23 ). Expression of TPX2 was significantly upregulated in renal cell carcinoma (RCC) and promoted the proliferative and invasive ability of RCC cells ( 24 ). In addition, it has been proposed that Absent in melanoma 1, Endoplasmic reticulum-Golgi intermediate compartment protein 1, Transmembrane emp24 domain-containing protein 3 and TPX2 are potential drug targets in PCa ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, TPX2 knockdown inhibited cell proliferation and invasion through decreased Akt phosphorylation and expression of MMP-9 and cyclin D1 ( 23 ). Expression of TPX2 was significantly upregulated in renal cell carcinoma (RCC) and promoted the proliferative and invasive ability of RCC cells ( 24 ). In addition, it has been proposed that Absent in melanoma 1, Endoplasmic reticulum-Golgi intermediate compartment protein 1, Transmembrane emp24 domain-containing protein 3 and TPX2 are potential drug targets in PCa ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of studies with OS or DFS data are presented in Table 1 . Of these studies, 3 evaluated gastric cancer, [ 22 24 ] 2 evaluated hepatocellular cancer, [ 12 , 27 ] and 1 each evaluated malignant astrocytoma, [ 19 ] prostate cancer, [ 30 ] epithelial ovarian cancer, [ 20 ] bladder carcinoma, [ 25 ] colon cancer, [ 28 ] esophageal squamous cell cancer, [ 26 ] renal cell cancer, [ 21 ] and squamous cell lung carcinoma. [ 29 ] The quality scores of included studies varied from 5 to 9.…”
Section: Resultsmentioning
confidence: 99%
“…Independent studies showed that in most cases overexpression of TPX2 had a negative impact on the prognosis of various types of solid tumors, such as astrocytoma, [ 19 ] ovarian cancer, [ 20 ] renal cell cancer, [ 21 ] gastric cancer, [ 22 24 ] bladder cancer, [ 25 ] esophageal squamous cell cancer, [ 26 ] hepatocellular cancer, [ 12 , 27 ] colon cancer, [ 28 ] and lung cancer. [ 29 ] However, Pan et al [ 30 ] found that the expression of TPX2 in tumor tissues of patients with prostate cancer was not related to their survival time.…”
Section: Introductionmentioning
confidence: 99%
“…TPX2 gene encodes a microtubule-associated protein, which serves a vital role in mitotic spindle formation and chromosome segregation process [24,25]. The overexpression of TPX2 has been reported in many studies and related to poor clinical outcomes of multiple malignancies, such as lung cancer, thyroid carcinoma, clear cell renal carcinoma, gastrointestinal cancer, and hepatocellular cancer, implying the possibility that TPX2 can be used as a prognostic marker and potential therapeutic target in these tumors [26][27][28][29][30][31][32][33][34]. Furthermore, TPX2 was reported to be involved in the invasion of tumor cells by the elevation of MMP2 and MMP9 through AKT signaling in hepatocellular carcinoma [35,36].…”
Section: Discussionmentioning
confidence: 99%